2023
DOI: 10.1002/qj.4546
|View full text |Cite
|
Sign up to set email alerts
|

Warm conveyor belts as amplifiers of forecast uncertainty

Abstract: Warm conveyor belts (WCBs) are rapidly ascending air streams associated with extratropical cyclones. WCBs exert a substantial influence on the evolution of the large‐scale midlatitude flow and have previously been related to increased forecast uncertainty in case studies. This study provides a first systematic investigation of the role of WCBs for errors in medium‐range ensemble forecasts in the Atlantic‐European region. The study is enabled through a unique data set allowing for a Lagrangian detection of WCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Further work needs to be done to attribute the systematic errors in Rossby wave structure shown here to model limitations in the representation of diabatic processes". An important study in this direction by Pickl et al (2023) found that the forecast skill of the ECMWF ensemble is generally reduced when the WCB activity is high, and that WCB activity is particularly increased when the error growth is largest.…”
Section: Diabatic Outflows and Forecast Errorsmentioning
confidence: 99%
“…Further work needs to be done to attribute the systematic errors in Rossby wave structure shown here to model limitations in the representation of diabatic processes". An important study in this direction by Pickl et al (2023) found that the forecast skill of the ECMWF ensemble is generally reduced when the WCB activity is high, and that WCB activity is particularly increased when the error growth is largest.…”
Section: Diabatic Outflows and Forecast Errorsmentioning
confidence: 99%
“…The WCB communicated the forecast error from small scales to the upper troposphere and downstream, which led to the missed onset of the block. Other studies also point to the amplification of errors in the WCBs (Pickl et al., 2023) or highlight the generation of errors in potential temperature and potential vorticity in the WCBs, which can lead to downstream errors in the Rossby wave pattern (Berman & Torn, 2019; Martínez‐Alvarado et al., 2016). Moreover, teleconnections from the Caribbean and North Pacific region affect the occurrence of large‐scale weather regimes, including blocking, in the European region (Michel & Rivière, 2011; Michel et al., 2012) and the teleconnection itself is again modulated by WCB activity (Quinting et al., 2024).…”
Section: Introductionmentioning
confidence: 99%
“…As WCBs and their impact on the large-scale flow are sensitive to the conditions provided by the background flow (e.g. low-level moisture supply (Schäfler and Harnisch, 2015) or baroclinicity (Grams et al, 2018)), WCBs act as a dynamical hinge between the lower and upper troposphere and between the synoptic and large scale, which makes WCBs very relevant for the growth and propagation of forecast errors (Martínez-Alvarado et al, 2016;Berman and Torn, 2019;Maddison et al, 2019;Pickl et al, 2023).…”
Section: Introductionmentioning
confidence: 99%